'Smart – not only intelligent!' Co-creating priorities and design direction for 'smart' footwear to support independent ageing. Issue 3 (2nd September 2019) - Callari, Tiziana C.; Moody, Louise; Magee, Paul; Yang, Danying
ABSTRACT: With an ageing population there is a growing need for technology that enables older adults to live independently for longer. The EU Horizon2020 funded MATUROLIFE project is focused on developing solutions that embed smart textiles to support well-being and independence in older adults. The study described here aimed to explore and initiate development of 'smart' footwear embedding assistive technology. A qualitative research strategy was employed including interviews with 37 older adults and co-creation activities with 56 older adults. Participants were recruited from eight European countries (Belgium, France, Germany, Italy, Poland, Spain, Turkey, and United Kingdom). The results detail the specific needs that older adults have in relation to footwear based on the daily activities they take part in. Participants shared their footwear fashion preferences, as well as their priorities for assistive functionality. A set-of co-created priorities and concept ideas are presented that consider how footwear might enable independent ageing.